Sensitivity of silicon photovoltaic converters to the light incidence angle on their receiving surface - Kirichenko, M. V.; Kopach, V. R.; Zaitsev, R. V.; Bondarenko, S. A. (Астропринт, 2009)
The results of output parameters dependences researches for multijunction silicon photovoltaic converters (PVC) upon solar radiation incidence angle on their receiving surface are presented. It has been shown that for improving of PVC efficiency is necessary to achieve the increased values of minority charge carriers lifetime in their base crystals as well as the optical reflection coefficient for metal/Si boundaries (interfaces) inside multijunction PVC, while for using multijunction PVC in the optical location systems the forced reduction of these values is reasonable.

Наведено результати досліджень залежностей вихідних параметрів багатоперехідних кремнієвих фотоелектричних перетворювачів (ФЕП) від кута падіння сонячного випромінювання на їх приймальну поверхню. Показано, що для збільшення ККД ФЕП необхідно забезпечити підвищені значення часу життя неосновних носіїв заряду в базових кристалах та коефіцієнта оптичного відбиття від границь метал/Si всередині багатоперехідних ФЕП, у той час, як при використанні багатоперехідних ФЕП у системах оптичної локації визначення напряму розповсюдження випромінювання доцільним є примусове зниження цих величин.
Чутливість кремнієвих фотоелектричних перетворювачів до кута падіння світла на їх приймальну поверхню
Keywords: photoconverter; photovolt; light incidence angle; reflection coefficient; parameters; електрична енергія; коефіцієнт відбиття; сонячне випромінювання; фотовольт; напруга